Studying Some of Immunological Parameters of doges that Toxocara Infections in Saladinprovince - Alaa Mohammed Awwad (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study examined 60 stray dogs from both sexes and aged 3 months - 3 years old, included 30 stray dogs and 30 dogs clinically normal, served as a control group. Toxocara infection has detected in the College of veterinary medicine Health Center in Tikrit city. Clinical signs were observed, the study groups divided to two groups one of these groups infected by the parasites of the study and other group was control the result appear immunological changes for protein levels in study groups, represented with significant differences was reported between toxocariasis group and healthy control in terms of Complement 3 proteins (33.21 ±14.18726, 35.57±15.56254), Complement 4 proteins (268.5±14.34, 146.06±17.83) although increased complement 3 level in toxocariasis group compared with healthy control, While the Complement 4 reported no significant differences increased between toxocariasis group and healthy control group. The immunoglobulins was reported highly significant differences in IgM (297.4±14.18726)in toxocariasis group compared with healthy control group (159 ±15.56), While revealed no significant decrease levels of IgG of toxocariasis group (760 ±14.34) compared with healthy control group (843±17.83). ToxocaraCanis induces an early immunological response that detected by presence of these antibodies and immunological markers against T.canis infection.